Rapid detection of Ganoderma disease of coconut and assessment of inhibition effect of various control measures by immunoassay and PCR - Muthusamy Karthikeyan; Krishnan Radhika; Ramanujam Bhaskaran; Subramanian Mathiyazhagan; Ramasamy Samiyappan; Rethinasamy Velazhahan (Plant Protection Science, 2006)
Molecular and immunological methods were applied for detecting the Ganoderma disease of coconut. Polyclonal antibodies (PAbs) raised against basidiocarp protein of Ganoderma were used. For the polymerase chain reaction (PCR) tests, the primer generated from the internal transcribed spacer region one (ITS 1) of ribosomal DNA gene of Ganoderma, which produced a PCR product of 167 bp in size, was used. Apparently healthy palms in two coconut gardens were tested for Ganoderma disease by ELISA test using basidiocarp protein antiserum. Field trials were laid out in these early-diagnosed palms for the management of the disease. Based on the ELISA results, Pseudomonas fluorescens + Trichoderma viride with chitin amended treatments arrested the multiplication of the pathogen and within 6 months showed an optical density (OD) below the level of infected plants. Integrated Disease Management (IDM) and fungicide tridemorph treated palms showed OD values below infection level within 7 months, and T. harzianum and P. fluorescens + T. viride treated palms showed OD values below infection level in 8 months.